The effects of different additives on the synthesis mechanism and lithium storage properties of corn straw-based carbon nanospheres - Zhang, Lan; Zhao, Qianqian; Yu, Kaifeng; Wang, Xiaofeng; Wang, Baoying (Ionics, 2023)
As a biomass derived carbon, corn stalk has a unique advantage in lithium-ion battery electrode application due to its wide distribution, environmental protection, low cost and renewable advantages. Unfortunately, the morphology of the natural carbon source is often fixed and single, which is difficult to meet our needs for morphology. In this work, ammonium persulfate, H 2 SO 4 and H 2 O 2 are added to adjust the form of biomass carbon during hydrothermal carbonization. Among them, when ammonium persulfate is used as the morphology control agent, the nanospheres have the most regular morphology. This is a spheroidization mechanism that accelerates the aromatization process by promoting the types of organic acids and aldehydes, so as to promote the explosion and growth of aromatic carbon cores. When it is used as the cathode material of lithium ion battery, the performance is stable at 787/581 mAh g −1 after 100/1000 cycles at 0.2 C/2 C, so it has excellent cycle stability.